ELECTRIC BIKES FOR GREEN MOBILITY IMPROVEMENT IN GILI IYANG, MADURA - Nugraha, Yoga Uta; Mubarok, Muhammad Syahril; Apsari, Retna (Universitas Airlangga, 2025)
This community service program is implemented in an island region that has limited access to electricity and fuel. This program is implemented on Gili Iyang Island, Sumenep, Madura. On the island, the only mode of transportation available is motorbikes and three-wheeled motorbikes due to limited and narrow roads. The price of gasoline reaches two to four times the normal price. Based on these conditions, the issue raised in this community service program is the use of electric bicycles for mobility, with the hope that it can also be a means of supporting the main tourist attraction of the island known as